IMPORTANCE OF FUNDED PENSION SCHEMES IN PROVISION OF PENSIONS: THE EXPERIENCE OF LATVIA AND THE OLD EU COUNTRIES - Jefremova, Jekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
During the past 20 years, pension reforms in the EU countries have lowered pension benefits. As a consequence of reforms each person’s responsibility for the result has increased. Examples of such reforms are those in Latvia (1995–2001), Germany (2001–2004) and the Netherlands (2004–2010). The essential part of future pension sufficiency is based on funded pension schemes, which are expected to prevent poverty and ensure the replacement of sufficient income in old age.The government defines a significant role to funded pension schemes. It is important to take into consideration major structural weaknesses in relation to social security. This includes such aspects as security and payment levels, risk management of savings and payment phases, tax implications and necessity of pension plan monitoring. These are all the problems to be solved in order to draw funded schemes as an integral part of retirement security among investors.This paper investigates the importance of funded pension schemes in securing pension in Latvia and in some old EU countries.